Exploring Accounting Application Adoption among East Java MSMEs through UTAUT Model - Winda Rein Nimas Tasia; Noval Adib; Virginia Nur Rahmanti (Jurnal Akuntansi, 2026)
This study aims to analyze the factors influencing the behavior of using accounting applications among Micro, Small, and Medium Enterprises (MSMEs) in East Java using the Unified Theory of Acceptance and Use of Technology (UTAUT) model modified with the addition of a trust variable. Data were collected through a survey of 326 respondents using accounting applications and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. The results showed that performance expectancy, social influence, and trust significantly influenced behavioral intention, while effort expectancy did not. Facilitating conditions and behavioral intention significantly influenced use behavior. Moderation tests showed that only experience moderated the effect of social influence on behavioral intention, while gender, age, and voluntariness of use did not significantly influence.